ANALISIS PENGARUH DPK, NPL, DAN ROA TERHADAP PENYALURAN KREDIT BPR DI KABUPATEN KEDIRI PERIODE 2014-2018 - Maria Eka Sihlestari; Henrycus Winarto; Mintarti Ariani (Jurnal Ekonomi dan Bisnis, 2020)
Essentially, the bank is financial institution which has the function to raise funds from thecommunity in the form of deposits, and the channel it back to the community in the form of creditor other. Credits is the main activities performed by Bank Perkreditan Rakyat, because it will bemakes a profit. However, the presenting credits will also provide a lot of risks that must bereceived or experienced by the BPR, because the risks that will be received or experienced aresourced to credit. Therefore, this researh is purpose to analys the effect of DPK, NPL, and ROA,on parcial althought simultan in contribute BPR credits. This researh conducted is quantitativeapproach use data panel regression method, and the data obtained are secondary data.According to the results of regression, the variables DPK and ROA have a significant influenceon credit distribution. While, the NPL variable doesn’t have a significant influence on creditdistribution.